Internet use identification as a learning platform for biology education students - Siti Zariati Jannah; Novi Fitriandika Sari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Advances in technology, especially the internet, provide significant benefits to education, but studies are needed to explain internet use by students. This study aims to identify the use of the internet as a learning platform for biology education students at Labuhanbatu University. This study used a survey method with a closed questionnaire as an instrument and interviews. The population in this study was 120 biology education students (semesters I, III, V, and VII), while the sample was taken by total sampling. The questionnaire was distributed via Google form and WhatsApp group containing 22 statements. The results of the study show that in accessing the internet, students use mobile phones more often (93%). The place where students often access the internet is at home (48%). The website that students frequently access is Google Scholar (40%). The identification aspect of the use of the internet as a learning platform for biology education students shows the time intensity of internet use (78.40%), reasons for internet access (3.87%), and the function of the internet as an educational facility (81.35%). The percentage of internet use among students with the highest acquisition is in semester VII, and the lowest is in the semester I. The high level of internet use by students needs to be one of the foundations for planning good lectures.AbstrakKemajuan teknologi khususnya internet memberikan manfaat signifikan pada pendidikan, namun diperlukan studi untuk menjelaskan penggunaan internet oleh mahasiswa. Penelitian ini bertujuan untuk mengidentifikasi penggunaan internet sebagai platform pembelajaran mahasiswa pendidikan biologi di Universitas Labuhanbatu. Penelitian ini menggunakan metode survei dengan kuesioner tertutup sebagai instrumen, dan wawancara. Populasi dalam penelitian ini adalah 120 mahasiswa pendidikan biologi (semester I, III, V dan VII), sedangkan penarikan sampel dilakukan secara total sampling. Kuesioner disebarkan melalui google form dan whatsapp group berisi 22 pernyataan. Hasil penelitian menunjukkan bahwa dalam mengakses internet, mahasiswa lebih sering menggunakan handphone (93%), tempat mahasiswa sering mengakses internet adalah rumah (48%), dan website yang sering diakses mahasiswa adalah google scholar (40%). Aspek identifikasi penggunaan internet sebagai platform pembelajaran mahasiswa pendidikan biologi menunjukkan intensitas waktu penggunaan internet (78,40%), alasan akses internet (3,87%), dan fungsi internet sebagai sarana pendidikan (81,35%). Persentase penggunaaan internet dikalangan mahasiswa dengan perolehan tertinggi berada pada semester VII, dan terendah pada semester I. Tingginya tingkat penggunaan internet oleh mahasiswa perlu menjadi salah satu landasan dalam merencanakan perkuliahan yang baik.